POLA ASUH ANAK DI KELUARGA MILITER (TNI) DI BATALYON ARHANUDSE 13 KUBANG PEKANBARU - Herawati "; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in Arhanudse Battalion. The purpose of this study to determine parenting in a military family in Battalion Arhanudse 13 Kubang Pekanbaru. This study, entitled "Parenting Children in Family Military (TNI) in the Battalion Arhanudse 13 Kubang Pekanbaru". What obstacles encountered in instilling parenting in a military family in Battalion Arhanudse 13 Kubang Pekanbaru. The sample of this study is that people using public transportation and the local community. Pengambikan samples was done by simple random sampling technique. Samples are numbered 5 NCO. The author uses descriptive qualitative method and the data were analyzed qualitatively. Instrument Data is observation, interviews, questionnaires and documentation. The results showed that not all military families who apply the method or style that is hard and authoritarian. There are applying Parenting Democratic but those that apply a blend of Parenting authoritarian and democratic. Although the military profession as a fact in daily communication with their families left an impression as a military and a father should act responsibly and be a role model for the children and his wife. Obstacles encountered both parents and children are generally caused by a lack of intensity or time to communicate with family. Sometimes there is a difference of perception, then there are many children who are not members of the military's authoritarian bias educated so that there is in violation of the ban that had been made by his parents. Investment in improving the character of parenting a child more quickly achieved in the respondent's family, because of their habit as parents always instilled submissive attitude toward rules and it also instilled by parents to their children. This is due to the influence of parents whose profession requires discipline against all the rules that apply in their environment.Keywords: parenting Military Families, Types of Parenting Children